2020
DOI: 10.1101/2020.11.23.20233155
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Disaggregating Asian Race Reveals COVID-19 Disparities among Asian Americans at New York City’s Public Hospital System

Abstract: There is growing recognition of the burden of COVID-19 among Asian Americans, but data on outcomes among Asian ethnic subgroups remain extremely limited. We conducted a retrospective analysis of 85,328 patients tested for COVID-19 at New York City’s public hospital system between March 1 and May 31, 2020, to describe characteristics and COVID-19 outcomes of Asian ethnic subgroups compared to Asians overall and other racial/ethnic groups. South Asians had the highest rates of positivity and hospitalization amon… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 23 publications
1
17
0
Order By: Relevance
“…Under the logic that patients with severe COVID-19 are more likely to be admitted to the hospita, l hospitalization rates could serve as a proxy for disease severity, and the vast majority of studies show Asian Americans have higher rates of hospitalization. 14,15,[29][30][31][32][33][34] Three studies in major health systems found 1.5 times higher odds of hospitalization compared to non-Hispanic Whites, similar to the 1.6 times higher risk found in the KFF study, which was the highest of any group. 15 Furthermore, a retrospective cohort study from 12 hospitals and 60 clinics in Minnesota (N=5577 with 12.2% Asians) found that Asian Americans had 2.4 times higher odds of hospitalization compared to non-Hispanic Whites; among Asian patients, those with limited-English proficiency had 1.6 times higher odds of hospitalization.…”
Section: Presenting Sicker and More Likely To Diesupporting
confidence: 56%
See 3 more Smart Citations
“…Under the logic that patients with severe COVID-19 are more likely to be admitted to the hospita, l hospitalization rates could serve as a proxy for disease severity, and the vast majority of studies show Asian Americans have higher rates of hospitalization. 14,15,[29][30][31][32][33][34] Three studies in major health systems found 1.5 times higher odds of hospitalization compared to non-Hispanic Whites, similar to the 1.6 times higher risk found in the KFF study, which was the highest of any group. 15 Furthermore, a retrospective cohort study from 12 hospitals and 60 clinics in Minnesota (N=5577 with 12.2% Asians) found that Asian Americans had 2.4 times higher odds of hospitalization compared to non-Hispanic Whites; among Asian patients, those with limited-English proficiency had 1.6 times higher odds of hospitalization.…”
Section: Presenting Sicker and More Likely To Diesupporting
confidence: 56%
“…9 While early studies were limited to specific states and counties and unadjusted, numerous subsequent studies confirmed a higher COVID-19 CFR for Asian Americans. [10][11][12][13][14][15][16] One of the largest studies to date is a Kaiser Family Foundation (KFF) analysis that used EPIC electronic health record (EHR) data of 332,956 COVID-19 patients from 399 hospitals across 21 states. 15 Compared to the U.S. population, the KFF sample had higher shares of Black and White patients and lower shares of Hispanic and Asian patients, although Asian patients still comprised 3% of the active patient population and about 11,000 COVID-positive cases.…”
Section: High Case Fatality From Covid-19mentioning
confidence: 99%
See 2 more Smart Citations
“…Within ethnic categories, differences in risk factors and health indicators have been observed for Latinx, Asian, and Black Americans. While some differences within ethnic categories have been attributed to country of origin [4][5][6], others are related to differences in lived experiences in the US which result from differential experiences with discrimination and stigma [7][8][9]. Research into health differences within ethnic categories has also led to observations about immigration related health patterns, like the healthy immigrant paradox, which does not seem to hold for all ethnic groups [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%